Effect of Graphene Powder on Banyan Aerial Root Fibers Reinforced Epoxy Composites. Issue 7 (3rd July 2021) - Ganapathy, T.; Sathiskumar, R.; Sanjay, M. R.; Senthamaraikannan, P.; Saravanakumar, S. S.; Parameswaranpillai, Jyotishkumar; Siengchin, Suchart
ABSTRACT: In this work, graphene was used as a filler for banyan aerial root fibers reinforced epoxy composites at various compositions. The synergetic effect of graphene and banyan fibers, on the physical and mechanical characteristics of the epoxy thermoset, was studied. The mechanical tests, hardness, water absorption behavior and morphology of the composites were studied. Significant improvement in tensile strength, flexural strength, shore D hardness and substantial reduction in the percentage of water absorption was observed. This paper also discusses the ideal proportion of banyan fibers with graphene powder for the development of the improved epoxy composites. The optimum concentration of the composites was observed at 4% of graphene powder in the 40% banyan fiber-reinforced hybrid epoxy composites. From the results, it is proved that graphene combined with 40% banyan fiber-reinforced epoxy hybrid composites will efficiently improve the strength of the composites.